2019
DOI: 10.1016/j.aninu.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pre-cecal phosphorus digestibility for corn, wheat, soybean meal, and corn gluten meal in growing Japanese quails from 28 to 32 d of age

Abstract: The optimization of dietary phosphorus (P) depends on precise details of the P availability in feed ingredients to avoid excess or deficient P in a mixed diet. This study was carried out to measure the apparent ileal digestibility of P for corn, wheat, soybean meal, and corn gluten meal in growing Japanese quails from 28 to 32 d posthatch. A total of 400 quail chicks were randomly distributed across 5 treatments with 4 replicates and 20 birds in each floor pen. The P-free diet (PFD) was formulated based on cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…As indicated in this experiment, underestimation of AIPD coefficients for tested ingredients could be overcome by correcting for basal EPL that was in agreement with Ghazaghi et al (2019) . In contrast to Ghazaghi et al (2019) , the significant differences among AIPD coefficients in feed ingredients were not disappeared by the correction of AIPD coefficients for EPL. The potential reason for this discrepancy is the lower EPL in the younger birds used in the present study than the older birds used in the study of Ghazaghi et al (2019) .…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…As indicated in this experiment, underestimation of AIPD coefficients for tested ingredients could be overcome by correcting for basal EPL that was in agreement with Ghazaghi et al (2019) . In contrast to Ghazaghi et al (2019) , the significant differences among AIPD coefficients in feed ingredients were not disappeared by the correction of AIPD coefficients for EPL. The potential reason for this discrepancy is the lower EPL in the younger birds used in the present study than the older birds used in the study of Ghazaghi et al (2019) .…”
Section: Resultsmentioning
confidence: 54%
“…More recently, Ghazaghi et al (2019) reported the apparent ileal and true ileal P digestibility values for corn, wheat, SBM, and CGM in growing quail from 28 to 32 d of age. Considering non-phytate P content of feed ingredients as the available P may increase the risk of overfeeding of P because the birds can utilize a portion of phytate-bound P in feed ingredients, and subsequently resulting in increasing P excretion ( Mutucumarana et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations